Предмет: Алгебра,
автор: espinosaAnanas
5/у +3 - 3/у =2-у/у2+3у
Ответы
Автор ответа:
0
Общий знаменатель ( y^2 + 3y ) = y( y + 3 )
y не равен 0 и ( - 3 )
( 5y - 3( y + 3 )/( y^2 + 3y ) = ( 2 - y )/( y^2 + 3y )
5y - 3y - 9 = 2 - y
2y + y = 2 + 9
3y = 11
y = 11/3
y = 3 2/3
y не равен 0 и ( - 3 )
( 5y - 3( y + 3 )/( y^2 + 3y ) = ( 2 - y )/( y^2 + 3y )
5y - 3y - 9 = 2 - y
2y + y = 2 + 9
3y = 11
y = 11/3
y = 3 2/3
Похожие вопросы
Предмет: Математика,
автор: dmitryi127
Предмет: Математика,
автор: kovtundominika05
Предмет: Математика,
автор: aluakalmaganbetova
Предмет: Математика,
автор: Dan156